Primary hydatid cyst of erector spinae muscle of upper back - Illahi, Mir Fazil; Gani, Mubashir; Malik, Ajaz Ahmad (International Journal of Research in Medical Sciences, 2024)
Hydatid disease is a zoonosis caused by an infection with the larvae of the tapeworm Echinococcus granulosus, it mostly involves liver and lungs but it may exceptionally affect muscle. We report the case of a 29 years old man who was admitted to our surgical clinic with a primary hydatid cyst in erector spinae muscle of upper back diagnosed by clinic examination, imaging and serological testing. The treatment was a complete pericystectomy and chemotherapy by antiparasitic drugs. Hydatid disease is an endemic disease in sheep-producing regions. In human, this disease involves usually the liver and the lungs and exceptionally the muscle. The diagnosis may be challenging, as it should consider arguments such as history, physical examination, imaging and serological testing. The best treatment is pericystectomy with perioperative chemotherapy to reduce risk of occurrence. The hydatid cyst of erector spinae muscle is exceptional even in endemic area, the diagnosis may be challenging and the surgery is the gold standard of treatment.